Lion hearts - Jones, Dan, 1981- (Jones, Dan, 1981- Essex dogs trilogy., 2025)
"1350. The Essex Dogs have scattered. In Winchelsea, Loveday struggles to keep his tavern afloat in the aftermath of the Black Death. Nowadays, the only battles he fights are the ones within his own mind. In Windsor, Romford thrives as a squire at King Edward III's court, his days as an archer fading into memory. But when an unpaid debt threatens everything he's built, Romford must call upon the lessons he learned all those years ago: be cunning. Be ruthless. Be quick. With England still reeling from the Death and a new threat from Spain on the rise, the kingdom's future has never been more uncertain. Each man had reasons for leaving the Essex Dogs behind. But a lifelike that isn't so easily forgotten. And for these men the fighting isn't over yet"--